Description of an Integrated and Dynamic System to Efficiently Deal With a Raging COVID-19 Pandemic Peak - Agnoletti, Vanni; Gamberini, Emiliano; Circelli, Alessandro; Martino, Costanza; Santonastaso, Domenico Pietro; Bolondi, Giuliano; Bastoni, Giorgia; Spiga, Martina; Ceccarelli, Paola; Montaguti, Luca; Catena, Fausto; Poletti, Venerino; et al. (Frontiers in Medicine, 2022)
Background To describe an innovative and functional method to deal with the increased COVID-19 pandemic-related intensive care unit bed requirements. Methods We describe the emergencial creation of integrated system of internistic ward, step-down unit and intensive care unit, physically located in reciprocal vicinity at the same floor. The run under the control of a single intensive care staff, sharing clinical protocols and informatic system, following a single director supervision. The intention was to create a dynamic and flexible system, allowing for rapid and fluid patient admission/discharge, depending on the requirements due to the third Italian peak of COVID-19 pandemic in March 2021. Results 142 COVID-19 patients and 66 non-COVID-19 patients were admitted, no critical patient was left unadmitted and no COVID-19 severe patients referring to our centre had to be redirected to other hospitals due to bed saturation. This system allowed shorter hospital length-of-stay in general wards (5.9 ± 4 days) than in other internistic COVID-19 wards and an overall mortality in line with those reported in literature despite the peak raging. Conclusion This case report shows the feasibility and the efficiency of this dynamic model of hospital rearrangement to deal with COVID-19 pandemic peaks.